Parentally-derived baby food: crop milk in captive-reared doves impacts growth and microbiome composition - Orr, Kristen N (East Carolina University, 2021)
Many animals have evolved parental care strategies to invest in their offspring and consequently improve their chances of survival and future reproductive success. Some produce few young that they invest in heavily with the production and provisioning of milk. Milk is a nutritious substance produced from the body of a parent and fed to offspring, pre- or post-parity. It occurs in many diverse animal taxa and provides a variety of nutritional benefits. This thesis combines a comprehensive literature review and an experimental study to examine how milk production arose and how it contributes to offspring fitness. In Chapter 1, I define "milk" and review its occurrence in diverse animal taxa. After describing and comparing the types of milk seen in mammals, birds, amphibians, teleost fish, cartilaginous fish, echinoderms, arachnids, hymenopterans, dipterids, cockroaches, isopods, earwigs, and mollusks, I investigate two main topics. First, I explore how and why some animal lineages evolved the ability to produce milk. Certain ecological factors likely predispose animals to milk production, whether directly or indirectly. These include unpredictable food availability, inaccessibility of parental diet, high predation risk, and extreme environmental conditions. I then investigate what factors determine where milk production evolves on the parent's body. It is likely that milk production evolved in structures that originally served secretory functions that were later exapted to serve an additional nutritive function. In Chapter 2, I focus on crop milk and its effect on the growth and gut microbiome compositions of captive-reared ring-necked doves (Streptopelia risoria). Young pigeons and doves (members of the family Columbidae) are fed crop milk, a nutritious substance synthesized in the crops of their parents. When hand-rearing columbids, specialized formulas are used that mimic the nutritional composition of crop milk. However, the success rates of chicks fed with these formulas is low, raising the possibility that essential microorganisms present in crop milk, but missing from the formulas, are responsible. I performed an experiment to determine how crop milk affects the growth and gut microbiome composition of captive-reared doves. Ring-necked dove chicks were raised on three different diets: 1) natural crop milk diet, raised by parents, 2) formula diet, raised by hand and 3) formula diet plus inoculations of crop milk, raised by hand. My results revealed that parentally-delivered crop milk improved chick growth rate and resulted in a richer and more diverse microbiome composition at earlier life stages. Inoculating hand-raised chicks with small amounts of crop milk resulted in an earlier onset of rapid growth when compared to hand-raised chicks that did not receive inoculations. This suggests that crop milk-associated microorganisms present in the inoculation may have shortened the initial "stalling" period that occurs before grow rate sharply increases in formula-raised chicks. Shortening this period of time could be important as this was when mortality in formula-raised chicks was highest. Once this inoculation method is refined, it could be used to improve success rates of traditional formula diets. Overall, this thesis provides insight into the various forms and mechanisms of milk. By reviewing what is known about milk production in diverse animal taxa, it has highlighted interesting trends and identified areas where more research is needed. By presenting the results of an experiment comparing growth rates and microbiomes of doves raised with and without crop milk, it has underscored the nutritional potency of this substance and provided potential avenues to improve columbid husbandry practices.
Keywords: parental care; matrotrophy; histophagy; birds; pigeons; microorganisms; captivity; hand-rearing; diet manipulation; Pigeon milk; Columbidae--Physiology; Foster care of animals; Gastrointestinal system--Microbiology